Updating the basic educational program for teachers to-be in line with independent assessment of competence development - A. I. Mezentseva (Вестник Северо-Кавказского федерального университета)
Introduction. Modernization of teacher education involves the search for new solutions to improve the quality of training of teachers and assess the quality of their professional training. To solve this problem, centers for independent assessment of the formation of competencies of teachers to-be are being created, where students are tested to establish the level of assessment of the formation of competencies of teachers to-be. The independent assessment is related to an external assessment, the purpose of which is to identify gaps in the training of teachers and adjust the training process in the educational institution.Goal. Presentation of the updating of the basic educational program in line with independent assessment of the formation of competencies of teachers to-be.Materials and methods. The research is based on theoretical and empirical research methods. The article discusses the basic concepts for the field under study. An integrated approach based on systemic, activity-based, competence-based, criterion-based and level-based approaches is being implemented.Results and discussion. The article presents the actualization of the basic educational program in line with independent assessment of the formation of future teachers' competencies by developing a pedagogical model for the independent assessment of teachers’ competencies, which should solve the problem of teacher training (increase the level of professional competencies). The structural components of the model of independent assessment of future teachers' competencies are humanities, general pedagogical training, subject training, methodological training. At the same time, professional, communicative (teacher-student, teacher-parents) and general competencies are evaluated.Conclusion. The testing of this model began in the 2024 / 2025 academic year, and the first results of the testing will be available in 2027.